The Effects of pH and Cell Density to the Responses of Immobilized Cyanobacteria for Copper Detection - Kunasakaran, Rubban; Vijayan, Sughan; Wong, Ling Shing; Chai, Mee Kin (Engineering and Technology Publishing, 2014)
Rapid urbanization and industrialization lead to heavy metal pollution which poses a serious threat to human’s health. Thus, there is a continuing need to develop a device that can be easily used to monitor and detect the presence of heavy metal pollution. Whole cells e.g. cyanobacteria have been reported as potential bio-indicators for environmental heavy metals detection. However, the intensity of the biological responses of these cells is affected by pH and the cell density. In this paper, the effect of pH and cell density to the response of cyanobacteria Anabaena cylindrica to copper (Cu) is reported. The cyanobacteria were cultured and immobilized with agarose in cuvettes before the exposure to Cu solution (1.0 mg/L). The measurement was carried out with OD= 680 nm using a spectrophotometer, which indicated the changes of chlorophyll. The most significant response of the cells was measured at pH 8 and the optimal density of the cell for the detection was 500,000 cell/mL. This study was an important stage to determine the potential of A. cylindrica to be used in heavy metal detection.